Tethys and Apulia (Adria), 100 years of reconstructions - Jolivet, Laurent (Comptes Rendus. Géoscience)
The lost Tethys Ocean was the favorite topic of Jean Dercourt’s research. The Tethys project and his 1986 paper displaying detailed reconstructions in 9 plates from the Triassic to the Present was the beginning of a series of projects organized around large consortia associating scientists from the academic and industrial worlds. The most recent evolutions of these reconstructions show unprecedented images of the evolving geology, including tectonics and paleoenvironments, through time of this complex puzzle. Central to Tethyan tectonics, Apulia, or Adria, has been drawn with different geometries and dimensions from the first concepts by Emile Argand, Kenneth Hsü or John Dewey, to the recent reconstructions by Douwe van Hinsbergen or Paul Angrand. We review here the main reconstructions published since 1924 and the evolution of concepts and methods. We finally discuss the importance of this type of syntheses for understanding large-scale geodynamic processes.